The Contributing Factors to the Risk of Diabetes Mellitus among Indonesian Urban Workers - Mahmudah Mahmudah; Nailul Izza; Lely Indrawati; Astridya Paramita; Diah Indriani (Nurse Media: Journal of Nursing)
Background: Diabetes mellitus (DM) is a non-communicable disease (NCD) with a high morbidity rate and is the third leading cause of death in Indonesia. Some risk factors are associated with the risk of DM; yet, little is known about the effect of such factors on the occurrence of DM in an urban worker population.